Pengaruh Mobile Food-Ordering Application GoFood Terhadap Loyalitas Merek Restoran di Indonesia - Denissa Nadhira Jasmine (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
With the growth of mobile food ordering application services in Indonesia, especially Go-Food by Gojek, there has been a rise in the partnership between Go-food and restaurants, along with the growing number of users. Therefore, this research is conducted to find out whether the Go-food MFOA usage by Indonesian users has any ef ect on the Restaurant brand loyalty especially during the pandemic. This research will aso use variables such as MFOA satisfaction. Restaurant brand satisfaction and restaurant brand attachment to further test their involvement. The function of this research is to show the role of MFOA that af ects Restaurant Brand Loyalty and drives success in doing business in the restaurant industry. The population this research is targeting is the Indonesian citizens that use Go-food MFOA. With the datas collected by using a questionnaire this research has gotten 400 respondents with a Convenience Sampling method. That will be further analysed using the partial least square-structural equation modelling approach in SmartPLS. The results shows that in Indonesia MFOA satisfaction does not directly af ect Restaurant brand loyalty, however it will be af ected if it was mediated by restaurant brand satisfaction and restaurant brand attachment beforehand.Keywords— MFOA Usage, MFOA Satisfaction, Restaurant Brand Satisfaction, RestaurantBrand Attachment, Restaurant Brand Loyalty.